Alginat v dostavnih sistemih s prirejenim sproščanjem - Novak, Polona (Farmacevtski vestnik, 2008)
Controlled drug delivery systems frequently offer significant benefit in comparison with immediate release dosage forms from the efficiency and safety viewpoint. Controlled release can be achieved using various polymers. Alginateis naturally occurring polysaccharide extracted from kelp. It is linear polymer, composed of homopolymeric D-mannuronic and L-guluronic acid blocks and heteropolymeric blocks where the monomers alternate. An important property is the formation of two types of gel, i.e. an acid gel in acidic medium and ionotropic gel in the presence of multivalent cations. Due to its ability to gel and swell and some other properties, alginate is very suitable for the design of controlled release drug delivery systems. Furthermore, the preparation of alginate matrix under mild conditions enables also the incorporation of cells and biomolecules like proteins, enzymes and DNA with retention of full biological activity. By the selection of an appropriate type of alginate and structure and composition of drug delivery system time and/or region controlled delivery can be achieved.
Keywords: alginat; dostava zdravilnih učinkovin; polisaharidi